Diagnostic Value of PCR for Detection ofBorrelia burgdorferiin Skin Biopsy and Urine Samples from Patients with Skin Borreliosis - S. Brettschneider; H. R. Bruckbauer; Norbert Klugbauer; Heidelore Hofmann (1998)
ABSTRACT Skin biopsies of 36 patients with erythema migrans and acrodermatitis chronica atrophicans (ACA) before therapy and those of 8 patients after therapy were examined for Borrelia burgdorferi DNA by PCR. Skin biopsies of 27 patients with dermatological diseases other than Lyme borreliosis and those of 10 healthy persons were examined as controls. Two different primer sets targeting 23S rRNA (PCR I) and 66-kDa protein (PCR II) genes were used. PCR was performed with freshly frozen tissue (FFT) and paraffin-embedded tissue (PET). For FFT specimens of erythema migrans, 73% were positive by PCR I, 79% were positive by PCR II, and 88% were positive by combining PCR I and II. For PET specimens, PCR was less sensitive (PCR I, 44%; PCR II, 52%). For FFT specimens of ACA, PCR I was positive for two of five patients and PCR II was positive for four of five patients. B. burgdorferi was cultured from 79% of the erythema migrans specimens but not from any of the ACA lesions. Elevated B. burgdorferi antibodies were detected in sera of 74% of erythema migrans patients and 100% of ACA patients. All urine samples were negative by PCR II, whereas PCR I was positive for 27%. However, hybridization of these amplicons was negative. Sequencing of three amplicons identified nonborrelial DNA. In conclusion, urine PCR is not suitable for the diagnosis of skin borreliosis. A combination of two different primer sets achieves high sensitivity with skin biopsies. In early erythema migrans infection, culture and PCR are more sensitive than serology.